The Gold Coast Integrated Care Programme: The Perspectives of Patients, Carers, General Practitioners and Healthcare Staff - McMurray, Anne (Int J Integr Care, 2021)
INTRODUCTION: The Australian Gold Coast Integrated Care programme trialled an innovative model of care to proactively manage high risk patients with complex and chronic conditions in collaboration with general practitioners. The objective was to enhance coordination and continuity of care across primary and secondary health services from a single point-of-entry multidisciplinary coordination centre. This case study, embedded in the broader trial, analysed the perceptions of patients, healthcare staff and general practitioners on the adequacy, comprehensiveness, timeliness and acceptability of the new model of care to help inform the decision by the health service whether to adopt it beyond the trial. METHODS: This mixed method embedded, explanatory case study design included surveys of general practice staff and focus groups with patients, carers and coordination centre staff. Qualitative data were thematically analysed and findings merged with survey data in a narrative explanatory case report. DISCUSSION: Staff, patients, general practitioners and practice nurses were generally satisfied with services, coordination of care and information sharing but general practice staff satisfaction ratings declined over time. CONCLUSION: The programme enhanced care and coordination of services and was valued by patients and healthcare providers. Study results provide a rationale for adopting the model for those with chronic and complex conditions.